An Unconventional Look at a Historical Monograph. Analysis with Artificial Intelligence (AI) Tools - Jarzyńska, Katarzyna (Žurnalistikos tyrimai, 2021)
Goal and theses: The article aims to check the applicability of methods based on processing large sets of information in research in social sciences. Conception/research methods: The dynamic development of new research methods based on the automated processing of large data sets using artificial intelligence (AI) means that they are used in an increasingly wide range of disciplines, going beyond the field of exact and natural sciences. Text mining was combined with available CLARIN web applications and keyword extraction and analysis strategy, a combination of the YAKE! written in Python with the VOSViewer program for the visualisation of bibliometric networks. Results and conclusions: The study showed how automatic keyword extraction creates opportunities in social science research. The use of CLARIN and Google Pinpoint web tools in the analysis significantly facilitates working with a large body of texts and accelerates its analysis. Cognitive value/originality: The study indicates new research methods that can contribute to the development of social sciences. The perspectives for the implementation of the ways of dealing with large data sets are presented in work in research on society, and conclusions regarding the development of digital social sciences are formulated.